Solution for What is 67 percent of 69:

67 percent *69 =

(67:100)*69 =

(67*69):100 =

4623:100 = 46.23

Now we have: 67 percent of 69 = 46.23

Question: What is 67 percent of 69?

Percentage solution with steps:

Step 1: Our output value is 69.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{69}={100\%}.

Step 4: Similarly, {x}={67\%}.

Step 5: This results in a pair of simple equations:

{69}={100\%}(1).

{x}={67\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{69}{x}=\frac{100\%}{67\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{69}=\frac{67}{100}

\Rightarrow{x} = {46.23}

Therefore, {67\%} of {69} is {46.23}

Solution for What is 69 percent of 67:

69 percent *67 =

(69:100)*67 =

(69*67):100 =

4623:100 = 46.23

Now we have: 69 percent of 67 = 46.23

Question: What is 69 percent of 67?

Percentage solution with steps:

Step 1: Our output value is 67.

Step 2: We represent the unknown value with {x}.

Step 3: From step 1 above,{67}={100\%}.

Step 4: Similarly, {x}={69\%}.

Step 5: This results in a pair of simple equations:

{67}={100\%}(1).

{x}={69\%}(2).

Step 6: By dividing equation 1 by equation 2 and noting that both the RHS (right hand side) of both
equations have the same unit (%); we have

\frac{67}{x}=\frac{100\%}{69\%}

Step 7: Again, the reciprocal of both sides gives

\frac{x}{67}=\frac{69}{100}

\Rightarrow{x} = {46.23}

Therefore, {69\%} of {67} is {46.23}